Does education affect energy behavior? Investigating the influence of educational attainment in Indonesia - Lilia Endriana; Djoni Hartono; Khoirunurrofik; Irfani Fithria Ummul Muzayanah (Social Sciences and Humanities Open)
This study investigates the causal relationship between educational attainment and various energy behaviors, including clean cooking fuel use, energy conservation practices, and energy-efficient technology adoption. Additionally, this study explores potential underlying mechanisms and regional heterogeneity. Utilizing a natural experiment from the 1978 school year extension policy in Indonesia, this study applies a regression discontinuity design and a two-stage least squares approach. Based on the 2017 National Socio-Economic Survey of Social Resilience Module data, the study results show that education significantly impacts the adoption of energy-efficient technologies. However, education has a limited impact on clean cooking fuel use, showing significance only in urban areas, and it does not significantly affect energy conservation behavior. These differences arise mainly due to variations in the costs involved, the technical understanding required, and structural factors such as affordability and accessibility. Further analysis reveals that education enhances income and access to information sources but does not substantially improve energy-saving knowledge. These varying effects suggest that education alone is insufficient in driving sustainable energy behavior. This implies the need for complementary measures such as clean energy subsidies, targeted behavioral campaigns, and expanded access to clean energy infrastructure (particularly in rural areas). Moreover, given education’s role in improving access to information, public communication through mass and digital media could play a vital role in encouraging sustainable energy practices.